2017
DOI: 10.1007/s10554-017-1286-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical deformation in adult patients with unrepaired aortic coarctation

Abstract: Aortic coarctation is a congenital heart disease that causes an increased left ventricular afterload, resulting in increased systolic parietal tension, compensatory hypertrophy, and left ventricular systolic and diastolic dysfunction. The speckle tracking is a new echocardiographic technique that allows the detection of subclinic left ventricular systolic dysfunction. The aim of this study was to detect early left ventricular dysfunction using mechanical deformation by echocardiography in adults with un-repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Avendaño-Pérez et al showed that adult patients with unrerpaied CoA had LVH, an increased LV mass, lower values of LV EF and GLS compared to controls, and that values of myocardial deformation were inversely related to LV mass. Also, GLS was reduced in patients with preserved EF, confirming the ability of this technique in detecting subclinical dysfunction ( 20 ).…”
Section: Left Ventricular Outflow Tract Obstructionsmentioning
confidence: 53%
See 1 more Smart Citation
“…Avendaño-Pérez et al showed that adult patients with unrerpaied CoA had LVH, an increased LV mass, lower values of LV EF and GLS compared to controls, and that values of myocardial deformation were inversely related to LV mass. Also, GLS was reduced in patients with preserved EF, confirming the ability of this technique in detecting subclinical dysfunction ( 20 ).…”
Section: Left Ventricular Outflow Tract Obstructionsmentioning
confidence: 53%
“…Avendaño-Pérez et al showed that adult patients with unrerpaied CoA had LVH, an increased LV mass, lower values of LV EF and GLS compared to controls, and that values of myocardial deformation were inversely related to LV mass. Also, GLS was reduced in patients with preserved EF, confirming the ability of this technique in detecting subclinical dysfunction (20). Indeed, regional longitudinal systolic myocardial deformations as assessed by strain rate (SR) were significantly reduced in a large sample of young normotensive patients years after successful CoA repair in the presence of a normal/increased LVEF.…”
Section: Echocardiographic Assessmentmentioning
confidence: 64%
“…In this paper, Aragao et al 1 showed a reduced left ventricular global longitudinal strain (LV‐GLS) before aortic coarctation repair and a progressive improvement after aortic coarctation stenting, despite the left ventricular ejection fraction remained unchanged over the time. Previous studies documented a decreased LV‐GLS in aortic coarctation, either before 2 and after 3,4 repair, showing that the ejection fraction in these patients is normal despite the presence of aortic coarctation, persisting arterial hypertension, or mild aortic valve disease. However, the life expectancy of these patients is reduced compared to healthy subjects.…”
Section: Figurementioning
confidence: 87%
“…It usually occurs near the ductus/ligamentum arteriosum, in a para-, pre-or postductal location, causing a discrete aortic lumen narrowing or a hypoplastic segment of the aorta [22,39,40] (Fig. 6a).…”
Section: Coarctation Of the Aorta (Coa)mentioning
confidence: 99%